'Schooling at Home' in Ireland during COVID-19': Parents' and Students' Perspectives on Overall Impact, Continuity of Interest, and Impact on Learning. Issue 2 (3rd April 2021) - Flynn, Niamh; Keane, Elaine; Davitt, Emer; McCauley, Veronica; Heinz, Manuela; Mac Ruairc, Gerry
Abstract : Educational disruption due to COVID-19 ushered in dramatically different learning realities in Ireland. Our research explored the experiences of children, young people and parents during the first period of 'schooling at home' (SAH) at the end of that academic year. An anonymous online survey, guided by social constructivist emphases, yielded responses from 2733 parents and 1189 students from primary and second-level schools. Substantial evidence emerged of parent-perceived and student-perceived negative psychosocial impacts of SAH on students. Further, our research clarified the exceptional stress experienced by parents in attempting to support SAH. A novel finding was student perceptions of having learned less during SAH, most likely due to significant declines in academic engagement. Recommendations for potential future periods of SAH include the need for innovative means of simulating socio-collaborative contexts, more flexible school supports based on unique home learning contexts, and enhanced psychological support for parents and at-risk children/young people. In addition, we recommend that further research in the Irish context should specifically investigate the perspectives and experiences of those from minority ethnic and lower socio-economic groups.